Research on the Provision of Education in the New South Wales Central School - Colin Boylan (Journal of Research in Rural Education, 1988)
A survey of parents, teachers and students in three rural New South Wales central (K-l 0) schools examined the provision of education. The study identified that parents and teachers regarded small class sizes as an important educational benefit as it allowed for a personalized and individualized curriculum. Teacher turnover was found to be decreasing in the central schools. Students and parents wanted a broader range of curriculum offerings which included Agriculture, Art and Foreign languages. Actual student retention rates to Year 12 were low yet three-quarters of all students would like to go onto Year 12.